Vertebroplasty in patients with multiple myeloma with vertebral compression fractures: protocol for a single-blind randomised controlled trial - Thomas Lund; Line Adsboell Wickstroem; Leah Carreon; Niels Abildgaard; Marianne Dyrby Lorenzen; Mikkel Østerheden Andersen (BMJ Open)
Introduction Multiple myeloma (MM) is a plasma cell cancer where about 1/3 of the patients present with pathological fractures at the time of diagnosis. Despite treatment, the majority of the patients will develop additional fractures. Because survival and prognosis has improved significantly over the last two decades for patients with MM, there is an increased need to focus on optimal fracture treatment. Traditionally, fracture pain is treated conservatively with opioids, bisphosphonates, bracing and radiation therapy. Vertebral augmentation has been used for the last three decades as a minimally invasive treatment option for vertebral compression fractures, but the evidence base for the efficacy is weak. We describe a trial assessing the impact of vertebroplasty on clinical outcome in the treatment of patients with MM with painful vertebral fractures.Methods 100 patients with MM with painful vertebral fractures will be randomised in a prospective, single-blinded, multicentre, clinical trial where patients are randomised to either usual care or usual care supplemented with vertebroplasty with a possibility of crossover 4 weeks after randomisation. The primary outcome will be change in Oswestry Disability Index at 4 weeks.Analysis Primary and secondary outcomes are assessed at baseline and at 4, 8, 26 and 52 weeks. Categorical data will be presented by means of frequencies and related percentages; continuous data will be displayed by means of descriptive statistics.Ethics and dissemination The study has been evaluated by the Regional Committees on Health Research for Southern Denmark (S-20200075) and notified and approved by the Region of Southern Denmark and listed in the internal record, journal no. 20/22355. All participants provide consent. The protocol will follow the SPIRIT (Standard Protocol Items for Randomized Trials) statement. The Danish Myeloma Patient Organization supports the study. Findings will be disseminated in peer-reviewed publications and presented at national and international conferences.Trial registration number NCT04533217.